Analisis Kemampuan Penalaran Siswa Melalui Media Calculate Your Path - Saragih, Sri Rahmah Dewi; Sirait, Syahriani; Sapta, Andy; Yusriani, Nida (JURNAL PENA EDUKASI, 2022)
Abstract: The purpose of this study was to determine the reasoning ability of students in solving the problem of summing up the AL-Mudzakir Kisaran Integrated PAUD students. This research method is descriptive qualitative. The subjects in this study were 21 students of the Integrated PAUD Al-Mudzakir Kisaran. The data collection technique used is a test designed in the calculate your path media. The results of data analysis showed that the category of students as much as 15.4%, the reasoning ability of students in the medium category there were 14. students as many as 65.6%, the reasoning ability of students in the low category there were 4 students as much as 19%. From the data analysis, the percentage of the average value of the achievement of students' reasoning abilities is 61%. so it can be concluded that the reasoning ability of Al-Mudzakir Integrated PAUD students is in the medium category.Keyword: student's reasoning ability, Calculate Your Path MediaAbstrak: Tujuan penelitian ini bertujuan untuk mengetahui kemampuan penalaran siswa dalam menyelesaikan soal penjumlahan pada siswa PAUD Terpadu AL-Mudzakir Kisaran. Metode penelitian ini adalah kualitatif deskriptif. Subjek dalam penelitian ini adalah 21 siswa PAUD Terpadu Al-Mudzakir Kisaran.  teknik pengumpulan data yang digunakan adalah tes yang di desain di dalam media calculate your path. Hasil analisis data menunjukkan bahwa kategori kemampuan penalaran siswa dalam kategori tinggi terdapat siswa sebanyak 15,4%, kemampuan penalaran siswa dalam kategori sedang terdapat 14.siswa sebanyak 65,6%, kemampuan penalaran siswa dalam kategori rendah  terdapat 4 siswa sebanyak 19%. Dari analisis data di peroleh persentase nilai rata-rata pencapaian kemampuan penalaran siswa adalah 61%. sehingga dapat disimpulkan bahwa kemampuan penalaran siswa PAUD Terpadu Al-Mudzakir tergolong dalam kategori sedang.Kata kunci: kemampuan penalaran siswa, media Calculate Your Path